Evaluation of flexor digitorum superficialis function in adolescent baseball players - Hiroyoshi Masuma, PT; Tomonori Kenmoku, MD, PhD; Kazuo Saito, OT; Masashi Kawabata, PT; Hiroyuki Watanabe, PT; Kazumasa Miida, PT; Kenji Onuma, MD, PhD; Koji Sukegawa, MD, PhD; Ryo Tazawa, MD, PhD; Yuya Otake, MD; Masashi Takaso, MD, PhD (JSES International, 2023)
Hypothesis and/or Background: Increased flexor digitorum superficialis (FDS) tendon activity can be a therapeutic target for elbow disorders in adolescent baseball players. The proportion of adolescent baseball players who can use FDS independently is unknown, and which finger is most often used remains unclear. This study investigated whether adolescent baseball players intentionally used FDS on each finger. Methods: Adolescent baseball players were recruited and assessed for FDS function for each finger using the standard technique. Results: Sixty-nine participants (mean age: 10.4 years) were recruited. Participants numbered 33, 56, 59, and 25 on the throwing side and those numbered 28, 46, 54, and 33 on the nonthrowing side could independently flex the proximal interphalangeal joint while holding their palms in the index, middle, ring, and small fingers, respectively. When assessing both throwing and nonthrowing participants, a significant number of participants could independently flex the proximal interphalangeals of the ring and middle fingers but had difficulty with the index and small fingers (P < .001). No significant difference was noted between the throwing and nonthrowing participants in any finger (P > .05). Discussion and/or Conclusion: One study reported that participating baseball players with elbow pain have more medial elbow joint space than those without pain symptoms. In another study on finger movements during pitching motion, the force of the thumb, index, middle, and ring fingers was greatest immediately before maximum external rotation. According to both reports, FDS function, especially in the index finger, can be a therapeutic target for medial-sided elbow injuries in adolescent baseball players.